Cultural Models of Male-Female Interactions in Folk Love Poetry (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The aim of the paper is to define cultural models of male-female interactions and the ideal male and female behaviours in folk lyric poetry. Taking a sociolinguistic perspective, the paper offers a possible interpretation of folk literature as well as the implications for future research in that direction. Anthology of Folk Lyric Poems, published by Matica srpska in 1969, serves as primary literature. As an already edited selection of motifs that have characterised folk art since the 15th century, the Anthology is considerad to be thier representative sample. The theorethical frame is provided by the theory of cultural models and its directive force on shaping the society. In the concluding remarks, the paper presents two causal lines or, more preciely, two models of male-female interactions in folk love poetry.
Keywords: folk lyric poems; love poetry; male-female interactions; cultural models; ideal behaviour